Vowel Phoneme in Javanese Language Wonosobo’s Dialect - Isma Farikha Latifatun Nuzulia (JELP Journal of English Language and Pedagogy, 2023)
This research was aimed to discuss the linguistics features, which was vowel phoneme, in Javanese language Wonosobo’s dialect. This study was extremely essential to recognize the vowel phoneme in Wonosobo since this regency abut on many regions uttering many dialects, which encouraged Wonosobo to have a mixed dialect. The research design was descriptive qualitative methods because this research analyzed the social complication, which was language phenomenon. After analyzing the data, it was found that vowel phoneme applied were [a], [i] [u], [e], [ə], [o], and [ɔ] with [I], [U] and [ɛ] as allophones.